Skin acidification with a water‐in‐oil emulsion (pH 4) restores disrupted epidermal barrier and improves structure of lipid lamellae in the elderly - Kilic, Ana; Masur, Clarissa; Reich, Hubert; Knie, Ulrich; Dähnhardt, Dorothee; Dähnhardt‐Pfeiffer, Stephan; Abels, Christoph (Journal of dermatology, 2019)
The pH of the skin surface increases with age and thus reduces epidermal barrier function. Aged skin needs appropriate skin care to counterbalance age‐related pH increase and improve barrier function. This confirmatory randomized study investigated the efficacy of water‐in‐oil (w/o) emulsions with either pH 4 or pH 5.8 in 20 elderly subjects after 4 weeks of treatment. After the treatment, the skin was challenged with a sodium dodecyl sulphate (SDS) solution in order to analyze barrier protection properties of both formulations. The pH 4 w/o emulsion resulted in a significantly lower skin pH compared with the pH 5.8 w/o emulsion and an improved skin hydration after 4‐week treatment. Further, the pH 4 emulsion led to more pronounced improvements in length of intercellular lipid lamellae, lamellar organization as well as lipid levels than the pH 5.8 emulsion. Following SDS‐induced barrier damage to the skin, the pH of all test areas increased, but the area treated with the pH 4 emulsion showed the lowest increase compared with baseline. In addition, even after the SDS challenge the skin area treated with the pH 4 emulsion still maintained a significantly increased length of intercellular lipid lamellae compared with the beginning of the study. This study provides evidence that topical application of a w/o emulsion with pH 4 reacidifies the skin in elderly and has beneficial effects on skin moisturization, regeneration of lipid lamellae and lipid content. Application of a pH 4 emulsion can improve the epidermal barrier as well as the stratum corneum organization in aged skin.